Blue Ocean Strategy and Competitiveness of Micro, Small and Medium Enterprises in Nigeria: Can Core Competence Mediate? - Edward G. EROMAFURU (Communications of International Proceedings, 2022)
The thrust of the study is to examine how consolidated constructs of Blue Ocean Strategy, mediated by core competence, align with MSMEs’ competitiveness. Avalanche of growing researches in strategies and entrepreneurships, notwithstanding, literatures that relate Blue Ocean Strategy to MSMEs’ competitiveness are exiguously scanty; and while plethora of studies have been conducted in advanced countries in related areas, rarely could be said about MSMEs in the manufacturing and service spectrum in Nigeria. The study anchoring on the re-constructionist theory, used cross-sectional research survey involving questionnaire, and sample size of 460 selected from 4, 572 MSMEs’ owners in entrepreneurship intensive states in the suburbs of Lagos, Port-Harcourt, Delta, Kano, and Onitsha,  arrived at through purposeful and stratified random sampling. Reliability and validity of instruments were confirmed. Linear and multiple regressions including exponential smoothening were engaged to validate the hypotheses and result has strengthened role of core competence mediating between Blue Ocean Strategy and MSMEs competitiveness. Results also underscored higher predictive impact of aggregated BOS constructs on competitiveness than when studied in detach. Study’s implications for theory, research value and future studies are also discussed.
Keywords: Blue Ocean Strategy; Core Competence; Competitiveness; MSMEs